OBIEKTY KRENOLOGICZNE W D OLNEJ CZĘŚCI DORZECZA WISŁY (PO ZLEWNIĘ DRWĘCY) - Choiński, Adam; Ptak, Mariusz (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
On the basis of hydrographic maps in the scale 1:50,000, an inventory of crenological objects in the lower part of the Vistula basin up to the Drwęca river basin in the south was made. The total number of theseobjects in the analyzed area is 308, with the highest number of solid sources – 161, followed by leakages – 125 and periodic sources – 17. The total efficiency of all outflows is very low, as it was estimated at 0.075 m3∙s–1. The most efficient source reaches only 1.0 dm3∙s–1, and only a few 0.7 dm3∙s–1.